Endogenous biosynthesis of n-3 long-chain PUFA in Atlantic salmon - Tom Mock; David Francis; Matt Jago; BD Glencross; RP Smullen; GM Turchini (2019)
A more efficient utilisation of marine derived sources of dietary omega-3 long-chain polyunsaturated fatty acids (n-3 LC PUFA) in cultured Atlantic salmon (Salmo salar L.) could be enhanced by nutritional strategies that maximise endogenous n-3 LC PUFA synthesis. The objective of the present study was to quantify the extent of n-3 LC PUFA biosynthesis and the resultant effect on fillet nutritional quality in large fish. Four diets were manufactured providing altered levels of dietary omega-3 substrate, namely 18:3n-3, and end-products, namely, 20:5n-3 and 22:6n-3. After 283 days of feeding, fish grew to in excess of 3000g and no differences in growth performance or biometrical parameters were recorded. An analysis of fatty acid composition and in vivo metabolism revealed that endogenous production of n-3 LC PUFA in fish fed a diet containing no added fish oil resulted in fillet levels of n-3 LC PUFA comparable to fish fed a diet with added fish oil. However, this result was not consistent among all treatments. Another major finding of this study was the presence of abundant dietary omega-3 substrate with the addition of dietary omega-3 end- product (i.e. fish oil) served to increase final fillet levels of n-3 LC PUFA. Specifically, preferential oxidation of dietary C18 n-3 PUFA resulted in conservation of n-3 LC PUFA from catabolism. Ultimately, this study highlights the potential for endogenous synthesis of n-3 LC PUFA to, partially, support a substantial reduction in the amount of dietary fish oil in diets for Atlantic salmon reared in seawater.